2004
DOI: 10.1080/13576500342000095
|View full text |Cite
|
Sign up to set email alerts
|

Human assessment of chimpanzee facial asymmetry

Abstract: In this study, facial asymmetry in chimpanzees was assessed using a technique that has traditionally been implemented in human studies. Image composites made of each half of chimpanzees' facial expressions were presented to humans with and without chimpanzee experience. The group of subjects with chimpanzee experience considered composites made of the left side of the chimpanzee faces as the most emotionally intense for the emotional categories of play, silent bared-teeth, scream face, and a neutral category. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 26 publications
4
10
4
Order By: Relevance
“…These results are consistent with cross-cultural research showing that people from cultures that value interdependence were found a) to have more contextualized self-concepts (e.g., Cousins, 1989;Kashima et al, 2004;Rhee et al, 1995) and b) to more often consider situational influences when making attributional inferences (Choi & Nisbett, 1998;Chua, Leu, & Nisbett, 2005;Mason, & Morris, 2010;Morris & Peng, 1994;Miyamoto & Kitayama, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with cross-cultural research showing that people from cultures that value interdependence were found a) to have more contextualized self-concepts (e.g., Cousins, 1989;Kashima et al, 2004;Rhee et al, 1995) and b) to more often consider situational influences when making attributional inferences (Choi & Nisbett, 1998;Chua, Leu, & Nisbett, 2005;Mason, & Morris, 2010;Morris & Peng, 1994;Miyamoto & Kitayama, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…It must be noted, however, that in primates the contrast between a left hemispheric dominance for positive emotions (food rewards, sex and positive social situations) and a right hemispheric dominance for negative emotions (fear and aggression) has not been found. Furthermore, most studies dealing with asymmetries in emotional expression in this phylogenetically advanced class of mammals, see [9,36,49,[78][79][80][81][82][83], have suggested a right hemisphere dominance across negative and positive emotions, which appears consistent with the right hemisphere model of emotional asymmetry.…”
Section: Models Of Hemispheric Asymmetries For Emotions Transposed From Human To Animal Studiessupporting
confidence: 52%
“…Now, since, in humans, different kinds of behavioral, functional or anatomical asymmetries have been detected for each stage of this interaction between the brain and the body, these asymmetries could also be present in animals. The second (more factual) reason is that while asymmetries in emotional communication equivalent to those observed in humans have been documented only in primates (e.g., [9,36,49,79,80,82,83], see reviews in [10,11]), and in few other social mammals, such as domestic pigs [15], asymmetries concerning the brain-body interactions have also been documented in animals belonging to more primitive levels of phylogenetic evolution. Furthermore, it must be noted that in animal behavior research, a distinction must be made between a cue and a communicatory signal, because an outward behavior stemming from an emotional response to a situation does not need to serve a communicative meaning.…”
Section: Comparative Analysis Of Components and Stages Of Emotional Processing That Could Contribute To A Better Integration Between Humamentioning
confidence: 99%
“…Second, also using images obtained during typical intraspecies interactions, raters have quantified the degree of difference in the left and right orofacial mouth regions during different expressions. From the chimerics, human subjects have reported that the two left halves of the face were judged to be more expressive than the two right halves in chimpanzees, baboons, and, to a lesser extent, rhesus macaques . For the production of species‐specific facial expressions, in general, left hemiface asymmetries (indicative of a right hemisphere asymmetry) have been reported in chimpanzees, baboons, and rhesus macaques .…”
Section: Primate Lateralitymentioning
confidence: 99%